Education Phenomenon in Terms of “Metaphysics of Man” - G. K. Saikina (Высшее образование в России)
The purpose of this article is to reveal the resources of “metaphysics of man” for understanding the phenomenon of education. The creativity of “metaphysics of man” based on understanding a man as a self-founded, free and self-creating creature, allows taking education as a process of molding, forming a person from himself and thereby affirming his anthropological foundations and ideals. Education can be defined as a fundamental characteristic of anthropic identity. The conclusion that the deep meaning of education is in line with the goal of human metaphysics, which consists of the self-elevation of a person above himself and attainment of himself is substantiated. Scheler’s concept of an “educated creature” was taken as an example of a bearer of a metaphysical relation to education, the essential features of which are ontological participation, the culture of the soul, openness to others, and living integrity, freedom, decency, guidance by common sense. The novel nature of the study is in the substantiation of the heuristic meaning of the comparative analysis of the institutional and metaphysical dimensions (modes of existence, aspects) of the educational process, which appeared to us in the form of individual models of education. The institutional and metaphysical models of education differ from each other: 1) according to the forms of communication between the teacher and the student (vertical or subject-object, and horizontal or subject-subject relations respectively); 2) according to the predominance of one of the educational aspects: teaching or learning (the dominance of teaching or the dominance of learning and self-learning); 3) according to the way the student relates to education (consumer relation or relation to education as an inherent value). The main difference between these models is anthropological: whether a person has made a choice in favor of the metaphysical dimension of life. Allowing moving away from practical relation to the education process, the metaphysical model of education introduces a true axiological meaning into it, affirming the commitment to the social and individual good.